2015
DOI: 10.1016/j.rbmo.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of CAG and GGN repeats of androgen receptor gene in women with polycystic ovary syndrome

Abstract: One characteristic of polycystic ovary syndrome (PCOS) is hyperandrogenism, which may be related to the activity of androgen receptor (AR). This study was designed to investigate the polymorphism of CAG and GGN repeats in the AR gene in women with PCOS. The frequency distributions of CAG and GGN repeat alleles, as well as their X-inactivation patterns, were compared between 76 age-matched normal women (control group) and 80 women with PCOS (PCOS group). The expression of AR mRNA in the ovarian tissues of seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…It has reach a consensus that overproduction of ovarian androgen is a pivotal pathologic feature of PCOS. [16,17] Series of intracellular and extracellular signaling pathways involved in PCOS pathogenesis have been impressed by steroidogenesis and androgen. [18,19] Prenatal androgen exposure and adolescent studies suggest that early androgen excess acts as an initiating factor of PCOS, but it still needs to confirm these hypothesis relying on convictive evidences.…”
Section: Discussionmentioning
confidence: 99%
“…It has reach a consensus that overproduction of ovarian androgen is a pivotal pathologic feature of PCOS. [16,17] Series of intracellular and extracellular signaling pathways involved in PCOS pathogenesis have been impressed by steroidogenesis and androgen. [18,19] Prenatal androgen exposure and adolescent studies suggest that early androgen excess acts as an initiating factor of PCOS, but it still needs to confirm these hypothesis relying on convictive evidences.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses examining the relationship between CAG repeat lengths at AR and PCOS risk have concluded that they may not be major determining factors in PCOS etiology [ 111 , 119 , 120 ]. Apart from CAG repeat, other groups have concluded that a GGN repeat polymorphism and rs6152G/A polymorphism were also significantly associated with PCOS in Chinese women [ 121 , 122 ]. Thus, AR polymorphisms may exacerbate the hyperandrogenic phenotype of women with PCOS.…”
Section: Genetics Of Pcosmentioning
confidence: 99%
“…Hpall digests only unmethylated (active) DNA segments, leaving the undigested methylated (inactive) DNA template intact for amplification. Digested and mock-digested genomic DNA from the same woman were amplified using PCR with primers, as previously described [ 36 ]. The forward primer was 5(6)-carboxyfluorescein-labelled.…”
Section: Methodsmentioning
confidence: 99%